EFFECTIVENESS OF MULTIMEDIA TECHNOLOGIES (ResearchJet Journal of Analysis and Inventions, 2021)
The article considers the possibilities of using some modern computer and multimedia technologies in the educational process at the Department of Botany Gulistan State University.